Superior-Order Curvature-Correction Techniques for Voltage References - Popa, Cosmin Radu (Springer US : Imprint: Springer, 2009)
Superior-Order Curvature-Correction Techniques for Voltage References is dedicated to the analysis and design of voltage reference circuits and evaluates improving their temperature behavior by implementing superior-order curvature-correction techniques. The author begins with the study of biasing current references with controllable temperature dependencies. That is followed by examining simple zero-order and first-order curvature-corrected voltage reference circuits which leads into the final topic of the analysis of superior-order curvature-correction techniques. The material includes a number of simulations which validate the estimated results. In some cases, the first-order analysis is completed by the examination of second-order effects that influence the circuits' operation. Superior-Order Curvature-Correction Techniques for Voltage References is useful for engineers and researchers in the area of analog and mixed-signal CMOS VLSI design.